Rancang Bangun Sistem E-Book : (Studi Kasus: Perpustakaan Pendidikan Matematika, FKIP, Universitas Pattimura) - Vederico Pitsalitz Sabandar (Pusat Riset dan Inovasi Nasional, 2022)
The rapid development of information and communication technology has opened new opportunities in the world of education, one of which is through the digitalization of academic reading materials. The E-Book system has become a relevant solution to improve accessibility and efficiency in the use of learning resources. This research aims to design and develop an E-Book system to be implemented in the Library of the Mathematics Education Study Program, Faculty of Teacher Training and Education, Pattimura University. This study uses a software development method, namely the waterfall method. The system is built using the CodeIgniter Framework, which applies the MVC concept, where the programming language used is PHP, and MySQL serves as the database server. In designing the system, the UML model is applied and a prototype is created to illustrate the system's interface display. Meanwhile, system testing is conducted using the Black Box Testing method. The results of this study indicate that the E-Book system functions well in terms of functionality, with no errors found, and is able to accelerate the process of searching, downloading, and uploading digital book data independently by students.